2017
DOI: 10.1111/andr.12449
|View full text |Cite
|
Sign up to set email alerts
|

Effect of testosterone supplementation on nitroso‐redox imbalance, cardiac metabolism markers, and S100 proteins expression in the heart of castrated male rats

Abstract: The aim of this study was to investigate the effects of castration and testosterone supplementation on nitroso-redox status, cardiac metabolism markers, and S100 proteins expression in the heart of male rats. 50 male Wistar rats were randomized into five groups with ten animals each: group 1: control intact (CON); group 2: sham operated (Sh-O); group 3: sesame oil-treated rats (S-oil); group 4: gonadoectomized (GDX); and group 5: gonadoectomized rats treated with testosterone (GDX-T) for 8 weeks. Our results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
2
3
1
Order By: Relevance
“…These observations suggest that DHT is responsible for the detrimental effects on cardiac function/morphology induced by testosterone. This is in agreement with our previous reports showing DHT as an inductor of myocardial damage (Regouat et al, 2018).…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…These observations suggest that DHT is responsible for the detrimental effects on cardiac function/morphology induced by testosterone. This is in agreement with our previous reports showing DHT as an inductor of myocardial damage (Regouat et al, 2018).…”
Section: Resultssupporting
confidence: 94%
“…Interestingly, the role of these enzymes' activities in the absence (as in gonadectomized animals) or in states of decreased circulating testosterone is poorly understood. We showed that ORX rats had a significant increase in 5α-reductase expression without changes in aromatase expression, our results suggested a cross-modulation of the activities of these enzymes since inhibition of their activities induced divergent effects in acute I/R-induced myocardial damage (Regouat et al, 2018).…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…In spite of our findings, one study showed that castration of male rats reduced the contractility of isolated myocytes and increased the accumulation of collagen fibers around blood vessels in the heart. Also, the percentage of fibrotic tissue in the heart of these animals was high (48). It seems that their findings are in spite of our findings.…”
Section: Discussioncontrasting
confidence: 88%